Colour-Difference Measurement Method for Evaluation of Quality of Electrolessly Deposited Copper on Polymer after Laser-Induced Selective Activation - Gedvilas, Mindaugas (Sci Rep, 2016)
In this work a novel colour-difference measurement method for the quality evaluation of copper deposited on a polymer is proposed. Laser-induced selective activation (LISA) was performed onto the surface of the polycarbonate/acrylonitrile butadiene styrene (PC/ABS) polymer by using nanosecond laser irradiation. The laser activated PC/ABS polymer was copper plated by using the electroless copper plating (ECP) procedure. The sheet resistance measured by using a four-point probe technique was found to decrease by the power law with the colour-difference of the sample images after LISA and ECP procedures. The percolation theory of the electrical conductivity of the insulator conductor mixture has been adopted in order to explain the experimental results. The new proposed method was used to determine an optimal set of the laser processing parameters for best plating conditions.